Tecno–indigenism. Martín Chambi and the duel of the images (El Taco en la Brea, 2018)
The photographic practice of Martín Chambi supposes something more than the accomplishment of admirable photographs. It is a transculturation operation in the framework of a semiotic dispute for authority and legitimacy against the colonial appropriation company that since the mid-nineteenth was making the scientific registration of the conquered regions managed by geographers, anthropologists, archaeologists, missionaries, expeditions and entrepreneurs . The counterpoint in the art of Chambi is unleashed by the aesthetic and affective plus with which it portrays a territory and produces a locality in tension with the demands of the primitivist prototypes of international modernism. We will have to take care to reduce the analysis of the images to their themes, concepts, classification schemes, types. We do not propose to explain them but to give an account of the duels, the tears and the tensions that cross them. The aim is to read their critical character in order to distinguish inaudible voices, lost claims, the challenge to the logocentric pattern that rests on the primacy of the word over the image. From this perspective, far from being an illustration or a document, photography dialogues in a singular way with the discursive mass grouped under the label of indigenismo.
Keywords: images; duel; indigenismo; Martín Chambi; photography